2021
DOI: 10.1371/journal.ppat.1009436
|View full text |Cite
|
Sign up to set email alerts
|

Resident bacteria contribute to opportunistic infections of the respiratory tract

Abstract: Opportunistic pathogens frequently cause volatile infections in hosts with compromised immune systems or a disrupted normal microbiota. The commensalism of diverse microorganisms contributes to colonization resistance, which prevents the expansion of opportunistic pathogens. Following microbiota disruption, pathogens promptly adapt to altered niches and obtain growth advantages. Nevertheless, whether and how resident bacteria modulate the growth dynamics of invasive pathogens and the eventual outcome of such i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…In mice, toxin production by S. aureus prevented elimination by the host immune system, which supported replication of Gram-negative bacteria in the lung and subsequent systemic infection ( Cohen et al, 2016 ). More recently, Wu et al (2021) demonstrated that S. chromogenes colonization in the upper respiratory tract of chickens promoted infection by Avibacterium paragallinarum, the etiologic agent of infectious coryza. These findings suggest that pioneer colonizers of the upper respiratory tract may facilitate infection and disease caused by opportunistic pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, toxin production by S. aureus prevented elimination by the host immune system, which supported replication of Gram-negative bacteria in the lung and subsequent systemic infection ( Cohen et al, 2016 ). More recently, Wu et al (2021) demonstrated that S. chromogenes colonization in the upper respiratory tract of chickens promoted infection by Avibacterium paragallinarum, the etiologic agent of infectious coryza. These findings suggest that pioneer colonizers of the upper respiratory tract may facilitate infection and disease caused by opportunistic pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The plausibility of this hypothesis is supported by a study in chickens that reported infection of the upper airway by Avibacterium paragallinarum (previously Haemophilus paragallinarum ) was dependent on co-colonization with Staphylococcus chromogenes , which released NAD + , a required factor for A . paragallinarum growth [ 16 ]. In the present study, we found that a variety of bacteria, including species resident in the upper airway of humans, released NAD + that was readily detectable in extracellular culture fluid and which supported growth of H .…”
Section: Introductionmentioning
confidence: 99%
“…In homeostasis, commensal bacteria exclude exogenous microorganisms and directly inhibit the growth of pathogens (Clark, 2020) resulting in the limited establishment of opportunistic pathogens such as A. paragallinarum in respiratory tract (Long et al, 2012). When host immunity is compromised, A. paragallinarum initiates colonization and invasion, which is facilitated by commensals like Gallibacterium anatis (Paudel et al, 2017), Ornithobacterium rhinotracheale (Morales-Erasto et al, 2016), and Staphylococcus chromogenes (Wu et al, 2021). Resident species constitute a new niche to allow A. paragallinarum colonization and virulence by providing public goods and disrupting host barriers (Hoare et al, 2021;Wu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…When host immunity is compromised, A. paragallinarum initiates colonization and invasion, which is facilitated by commensals like Gallibacterium anatis (Paudel et al, 2017), Ornithobacterium rhinotracheale (Morales-Erasto et al, 2016), and Staphylococcus chromogenes (Wu et al, 2021). Resident species constitute a new niche to allow A. paragallinarum colonization and virulence by providing public goods and disrupting host barriers (Hoare et al, 2021;Wu et al, 2021). Additionally, protection mediated by indigenous microbial communities including extensive horizontal gene transfer (McInnes et al, 2020) and antibiotic inactivation (Gjonbalaj et al, 2020) increases the antimicrobial tolerance and resistance of pathogens.…”
Section: Introductionmentioning
confidence: 99%